2017
DOI: 10.1016/j.jalz.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk score of sporadic late‐onset Alzheimer's disease reveals a shared architecture with the familial and early‐onset forms

Abstract: Our analysis confirms that the genetic factors identified for LOAD modulate risk in sLOAD and fLOAD and also sEOAD cohorts. Specifically, our results suggest that the burden of these risk variants is associated with familial clustering and earlier onset of AD. Although these variants are not associated with risk in the eADAD, they may be modulating age at onset.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
105
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 54 publications
13
105
3
Order By: Relevance
“…Our results are similar to the findings from several recent studies examining the effect of SNP-based PRSs and their joint effect with APOE on AD risk and AAO. [20][21][22][23][24] In a study analyzing 21 AD risk- Although the conclusions from these published studies and our study are similar, the methods used for measuring the cumulative effect of SNPs differed. In these previously published studies, PRSs were not standardized to a general population and therefore difficult to interpret.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our results are similar to the findings from several recent studies examining the effect of SNP-based PRSs and their joint effect with APOE on AD risk and AAO. [20][21][22][23][24] In a study analyzing 21 AD risk- Although the conclusions from these published studies and our study are similar, the methods used for measuring the cumulative effect of SNPs differed. In these previously published studies, PRSs were not standardized to a general population and therefore difficult to interpret.…”
Section: Discussionsupporting
confidence: 50%
“…Several recent studies further demonstrated the combined effect of APOE and risk‐associated SNPs on AD risk . This finding has important implications in inherited risk assessment of AD.…”
Section: Introductionmentioning
confidence: 80%
“…154,155 The disadvantage of this model is lacking the relevant characteristics of AD, such as plaque formation and NFTs. Morimoto et al injected Aβ or Aβ [25][26][27][28][29][30][31][32][33][34][35] fragments alone or in combination with ibotenic acid into the hippocampus of rats. It was found that the neurons in CA1, CA4, and dentate gyrus were largely depleted, as well as the Aβ deposition present around hippocampus.…”
Section: Metal Ion Dysfunction-induced Ad Animal Modelmentioning
confidence: 99%
“…156 Laurent et al injected Aβ and Fe 2+ into the brain of rats and observed the elevation of oxidative stress, Aβ deposition, and memory dysfunction. 157 In addition, there are complex models combined with three kinds of factors, such as co-injecting Aβ [23][24][25][26][27][28][29][30][31][32][33][34][35] , AlCl 3 , and TGFβ1 into the lateral ventricle of rats. The decline of memory and learning ability, neuron loss, NFTs deposition, free radical system abnormalities, glial cell proliferation, and neuroinflammation were observed after 1 month.…”
Section: Metal Ion Dysfunction-induced Ad Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation